Gender-related differences in a process of the age-dependent alterations of the elements in monkey sino-atrial node - Hiroyasu Satoh (2018)
Gender differences in the trace elements of monkey sino-atrial (SA) node were investigated in a process of age-dependent alterations. Sixty hearts from Japanese and rhesus monkeys (30 male and 30 female) used were aged ranging from 1-day- to 30-year-old. The elements were analyzed using an inductively coupled plasma-atomic emission spectrometer (ICP-AES). Advancing age decreased all the trace elements. Ca, P, S and Mg significantly decreased. The correlation coefficients of Ca and P were -0.178±0.081 (p<0.05) and -0.088±0.022 (p<0.05) in male (n=30), and -0.095±0.026 (p<0.05) and -0.069±0.017 (p<0.05) in female (n=30), respectively. The age-dependent coefficients for Fe/Ca, Zn/Ca, Fe/P, Fe/S, Zn/S, Fe/Mg and Zn/Mg were exhibited markedly in male, but all was less in female. In gender-related differences, only a ratio of P/Ca (p<0.05) was significantly observed with ageing. The trace elements such as Cu, Se and Sn were less detected in the SA nodes. These results indicate that the age-dependent changes in the ratios of elements are appeared more rapidly in male monkey SA node, and the gender difference is observed in ratio of P/Ca. The different attenuations may be involved with the age- and gender-related SA nodal functions.